Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.2514/2.2161
|View full text |Cite
|
Sign up to set email alerts
|

Automated Design Optimization for the P2 and P8 Hypersonic Inlets

Abstract: An automated design methodology incorporating industry-standard Navier -Stokes codes and a gradient-based optimizer has been developed. This system is used to redesign the well-known NASA P2 and P8 hypersonic inlets. First, the Navier -Stokes simulations of the original P 2 and P8 inlet designs are validated using numerical convergence studies and comparison with wind-tunnel experimental data for the original inlets published by NASA in the early 1970s. Second, the P 2 and P8 inlets are redesigned with the obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Along the bodyside of the inlet, our simulations are in good agreement with the experimental data in the boundary layer region, however, an over-prediction in the core-flow region is observed. The numerical results compare well to others who have applied the sharp cowl approximation, however, prior works did not notice an over-prediction of the normalised Pitot pressures in the core flow [235][236][237]241]. These authors used a patched-grid approach by dividing the inlet into self-contained regions, in comparison to simulating the inlet in a tip-to-tail fashion, as done in this current work.…”
Section: Baseline Flowfieldsupporting
confidence: 80%
See 2 more Smart Citations
“…Along the bodyside of the inlet, our simulations are in good agreement with the experimental data in the boundary layer region, however, an over-prediction in the core-flow region is observed. The numerical results compare well to others who have applied the sharp cowl approximation, however, prior works did not notice an over-prediction of the normalised Pitot pressures in the core flow [235][236][237]241]. These authors used a patched-grid approach by dividing the inlet into self-contained regions, in comparison to simulating the inlet in a tip-to-tail fashion, as done in this current work.…”
Section: Baseline Flowfieldsupporting
confidence: 80%
“…Since the mid-1990s, several researchers have studied integrating high-fidelity Reynolds-Averaged Navier-Stokes (RANS) calculations into the hypersonic inlet design process. Gelsey et al [235] and Shukla et al [236,237] presented some of the first RANS-based design optimisation results for hypersonic inlets: throughout a series of papers, the authors presented redesigns of the P2 and P8 hypersonic inlets using NASA's NPARC and GASP codes coupled with the k-ε turbulence model. Hasegawa et al [238,239] also utilised the GASP code in an automated design optimisation of generic 2D inlets using the k-ω turbulence model.…”
Section: Background For Hypersonic Inlet Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Our confidence in rule-based gradients was high enough that we decided to run the optimizations with rule-based gradients. We obtained good optimization results in these domains [results which in the case of hypersonic inlets have been published in the aerodynamics engineering literature (Shukla et al, 1997)], and we believe that the results would have been less successful if we had not used rule-based gradients, although we have not been able to experimentally test this belief. uous, smooth, and defined everywhere.…”
Section: Other Domainsmentioning
confidence: 90%
“…We have found that using rule-based gradients results in good optimization performance in several other design domains. These domains include the design of racing yachts (Ellman et al, 1993;Schwabacher et al, 1994Schwabacher et al, , 1996, the design of exhaust nozzles for supersonic jets (Gelsey et al, 1996a), the design of inlets for hypersonic jets (Gelsey et al, 1995;Shukla et al, 1996Shukla et al, , 1997, and the design of inlets for supersonic missiles (Zha et al, 1996(Zha et al, , 1997. All of these domains use simulators that are more expensive than our airframe simulator.…”
Section: Other Domainsmentioning
confidence: 99%